Developmental Status of Children Operated for Esophageal Atresia with or without Tracheoesophageal Fistula Along with Maternal Stress, Their Quality of life, and Coping Abilities at AIIMS, New Delhi - Kumari, Vanita; Joshi, Poonam; Dhua, Anjan Kumar; Sapra, Savita; Srinivas, Maddur; Agarwala, Sandeep; Bhatnagar, Veereshwar (European Journal of Pediatric Surgery, 2019)
Introduction Esophageal atresia with or without tracheoesophageal fistula (EA with or without TEF) is one of the neonatal surgical emergencies requiring surgical intervention in the early neonatal period, influencing the developmental outcome in the operated children. This study was aimed to assess the developmental status of children operated for EA with or without TEF along with maternal stress, their quality of life (QOL), and coping abilities.Materials and Methods A descriptive cross-sectional survey was conducted on 51 children aged up to 5 years after EA with or without TEF repair and their mothers' in a tertiary care facility. The tools used were, namely, demographic datasheet of child and mother, anthropometry assessment, Developmental Assessment Scale for Indian Infants, and modified Vineland Social Maturity Scale for the developmental evaluation, Child Behavior Checklist (1.5–5 years) caregiver report form, Parental Stress Scale, WHOQOL BREF, and Coping Strategies Checklist.Results The majority of children had low weight (47.1%) and height (31.4%), for reference age. The overall and social developmental delay was observed in 40.7 and 37.5% of children, respectively, and few children (7.4%) had behavioral problems in the borderline range. Among the mothers, 47% had moderate stress and relatively poor QOL in environmental (60.1 ± 18.9) and psychological (60.8 ± 18.8) domains. The most commonly used coping strategy by the mothers was an emotional outlet (29.4%).Conclusion Developmental delay was present in children operated for EA with or without TEF caused significant stress among mothers, affecting their QOL for which the emotional outlet was the most commonly used coping strategy.
Keywords: developmental status; maternal stress; quality of life; coping abilities